Identify the roles of relationship marketing in account management of Ogilvy & Mather - Uzzaman, A.K.M. Shihab (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2013.